Kunjungan Rahmah El Yunusiyah ke Mesir Tahun 1957: Sebuah Kajian Historis - Imma Fatul Hasnah; Siti Fatimah (Jurusan Sejarah FIS UNP, 2026)
This study examines Rahmah El Yunusiyah's visit to Egypt in 1957 as one of the significant events in the history of Islamic education in Indonesia. Although the event has important historical value, studies that comprehensively discuss the chronology of Rahmah El Yunusiyah's visit based on historical sources remain limited. Most previous studies have focused on her educational thought and contributions to the development of Islamic education for women rather than examining the course of her visit to Egypt. This study aims to explain the chronology of Rahmah El Yunusiyah's visit to Egypt in 1957 and its historical significance. The research employed the historical method, which consists of four stages: heuristics, source criticism, interpretation, and historiography. Data were collected through library research, documentation, archival sources, and interviews with members of Rahmah El Yunusiyah's family and a lecturer at STIT Diniyah Puteri Padang Panjang. The findings indicate that Rahmah El Yunusiyah's visit to Egypt in 1957 took place in several stages, including preparation for departure, the visit to Egypt, travel to several Middle Eastern countries, and her return to Indonesia. The study further reveals that the visit was an important event in the history of Islamic education in Indonesia because it reflected international recognition of Rahmah El Yunusiyah's contribution to the development of Islamic education for women while providing a more comprehensive understanding of the historical significance of her visit to Egypt in 1957.